Virtual Space: Creating a Place for Social Support in Second Life. (May 2015) - Best, Kirsty; Butler, Stephanie
Drawing on the results of a study examining the use of Second Life as a platform for social support by people with myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS), the authors posit that virtual architecture needs to be designed to be inclusive to people with cognitive impairments. The ME/CFS Centre in Second Life allowed people who were socially isolated to forge social support systems across geographical distances. However, technological issues interfered with the development of participants' senses of community within the virtual space of the ME/CFS Centre. These difficulties with the designed landscape reveal that theorizations, and applications, of geography and disability, and inclusive web design, need to extend to the ways that virtual architectural structures are designed and furnished-if these spaces are to be inclusive.